Simultaneous Diarization and Separation of Meetings through the Integration of Statistical Mixture Models - Cord-Landwehr, Tobias; Boeddeker, Christoph; Haeb-Umbach, Reinhold (ICASSP 2025 - 2025 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
We propose an approach for simultaneous diarization and separation of meeting data. It consists of a complex Angular Central Gaussian Mixture Model (cACGMM) for speech source separation, and a von-Mises-Fisher Mixture Model (VMFMM) for diarization in a joint statistical framework. Through the integration, both spatial and spectral information are exploited for diarization and separation. We also develop a method for counting the number of active speakers in a segment of a meeting to support block-wise processing. While the total number of speakers in a meeting may be known, it is usually not known on a per-segment level. With the proposed speaker counting, joint diarization and source separation can be done segment-by-segment, and the permutation problem across segments is solved, thus allowing for block-online processing in the future. Experimental results on the LibriCSS meeting corpus show that the integrated approach outperforms a cascaded approach of diarization and speech enhancement in terms of WER, both on a per-segment and on a per-meeting level.
Keywords: diarization; source separation; mixture model; meeting

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Ultrafast Two‐Color X‐Ray Emission Spectroscopy Reveals Excited State Landscape in a Base Metal Dyad - Nowakowski, Michał; Huber‐Gedert, Marina; Elgabarty, Hossam; Kalinko, Aleksandr; Kubicki, Jacek; Kertmen, Ahmet; Lindner, Natalia; Khakhulin, Dmitry; Lima, Frederico A.; Choi, Tae‐Kyu; Biednov, Mykola; Schmitz, Lennart; et al. (Advanced Science)
Effective photoinduced charge transfer makes molecular bimetallic assemblies attractive for applications as active light‐induced proton reduction systems. Developing competitive base metal dyads is mandatory for a more sustainable future. However, the electron transfer mechanisms from the photosensitizer to the proton reduction catalyst in base metal dyads remain so far unexplored. A Fe─Co dyad that exhibits photocatalytic H2 production activity is studied using femtosecond X‐ray emission spectroscopy, complemented by ultrafast optical spectroscopy and theoretical time‐dependent DFT calculations, to understand the electronic and structural dynamics after photoexcitation and during the subsequent charge transfer process from the Fe(II) photosensitizer to the cobaloxime catalyst. This novel approach enables the simultaneous measurement of the transient X‐ray emission at the iron and cobalt K‐edges in a two‐color experiment. With this methodology, the excited state dynamics are correlated to the electron transfer processes, and evidence of the Fe→Co electron transfer as an initial step of proton reduction activity is unraveled.
Keywords: Photo; Xray

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: Xray

Hydrogen spillover through hydride transfer: the reaction of ZnO and ZrO2 with strong hydride donors - Benz, Michael; Bunjaku, Osman; Nowakowski, Michał; Allgaier, Alexander; Biswas, Indro; van Slageren, Joris; Bauer, Matthias; Estes, Deven P. (Catalysis Science & Technology)
Hydride donors such as DIBAL or CuH react with ZnO and ZrO2 via hydrogen spillover. This suggests that hydrogen spillover in catalysts based on these metal oxides may take place via initial hydride transfer and not via proton–electron transfer.
Keywords: Xray

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.
Keywords: Xray

New and Facile Preparation Method for Highly Active Iron Oxide Catalysts for CO Oxidation - Schlicher, Steffen; Schoch, Roland; Prinz, Nils; Zobel, Mirijam; Bauer, Matthias (Catalysts)
This work presents a new and facile route for the preparation of iron oxide-based catalysts supported on alumina, which enables the targeted synthesis of catalysts with an increased amount of isolated tetrahedrally coordinated iron centers compared to a conventional impregnation procedure, and therefore leads to an increase in activity for CO oxidation reaction. By a multi-step impregnation–calcination protocol, the catalysts were synthesized with iron loadings of between 1 and 10 wt%, and their catalytic activity was then compared with a 10 wt% loaded catalyst prepared by conventional single impregnation. With a loading of 8 wt%, the presented catalysts showed an improved catalytic activity regarding light-off and full conversion temperatures compared to this reference. Through the application of several analytical methods (PXRD, PDF, DRUVS, SEM, XAFS), the improved catalytic activity can be correlated with an increased amount of isolated iron centers and a significantly reduced fraction of agglomerates or particles.
Keywords: Catalysis

Extended Results for Effectiveness Study of an Augmented Reality App as Preparation Tool for Electrical Engineering Laboratory Courses - Alptekin, Mesut; Temmen, Katrin (Smart Technologies for a Sustainable Future: Proceedings of the 21st International Conference on Smart Technologies & Education. Volume 1)
This book includes the proceedings of the 21st International Conference on Smart Technologies & Education (STE2024). The "International Conference on Smart Technologies & Education" (STE) is an annual global meeting dedicated to the fundamentals, applications, and experiences in the field of Smart Technologies, Online, Remote, and Virtual Engineering, Virtual Instrumentation, and other related new technologies. Nowadays, online and smart technologies are the core of most fields of engineering and the whole society. Consequently, the motto of this year’s STE2024 was "Smart Technologies for a Sustainable Future". The STE conference is the successor of the long-standing annual REV Conferences and the annual meeting of the International Association of Online Engineering (IAOE) together with the EduNet World Association (EWA) and the International Education Network (EduNet). In a globally connected world, the interest in online collaboration, teleworking, remote services, and other digital working environments is rapidly increasing. In response to that, the general objective of this conference is to contribute and discuss fundamentals, applications, and experiences in the field of Online and Remote Engineering, Virtual Instrumentation, and other related new technologies like Cross Reality, Open Science and Big Data, Internet of Things and Industrial Internet of Things, Industry 4.0, Cyber Security, and M2M and Smart Objects. Another objective of the conference is to discuss guidelines and new concepts for engineering education in higher and vocational education institutions, including emerging technologies in learning, MOOCs and MOOLs, and Open Resources. This year, STE2024 has been organized in Helsinki, Finland as an onsite event supporting remote presentations, from March 6 until March 8, 2024. The co-organizers of STE2024 were the Arcada University of Applied Sciences, the International Association of Online Engineering (IAOE) together with the Global Online Laboratory Consortium (GOLC), the International Education Network (EduNet), and the EduNet World Association (EWA). STE2024 has attracted 140 scientists and industrial leaders from more than 40 countries

Effectiveness Study of an Augmented Reality App as Preparation Tool for Electrical Engineering Laboratory Courses - Alptekin, Mesut; Temmen, Katrin (Smart Technologies for a Sustainable Future)

Exercise-induced central and peripheral sympathetic activity in a community-based group of epilepsy patients differ from healthy controls - van den Bongard, Franziska; Gowik, Julia Kristin; Coenen, Jessica; Jakobsmeyer, Rasmus; Reinsberger, Claus (Experimental Brain Research)
Abstract Ictal and interictal activity within the autonomic nervous system is characterized by a sympathetic overshoot in people with epilepsy. This autonomic dysfunction is assumed to be driven by alterations in the central autonomic network. In this study, exercise-induced changes of the interrelation of central and peripheral autonomic activity in patients with epilepsy was assessed. 21 patients with epilepsy (16 seizure-free), and 21 healthy matched controls performed an exhaustive bicycle ergometer test. Immediately before and after the exercise test, resting state electroencephalography measurements (Brain Products GmbH, 128-channel actiCHamp) of 5 min were carried out to investigate functional connectivity assessed by phase locking value in source space for whole brain, central autonomic network and visual network. Additionally, 1-lead ECG (Brain products GmbH) was performed to analyze parasympathetic (root mean square of successive differences (RMSSD) of the heart rate variability) and sympathetic activity (electrodermal activity (meanEDA)). MeanEDA increased ( p < 0.001) and RMSSD decreased ( p < 0.001) from pre to post-exercise in both groups. Correlation coefficients of meanEDA and central autonomic network functional connectivity differed significantly between the groups ( p = 0.004) after exercise. Both patients with epilepsy and normal control subjects revealed the expected physiological peripheral autonomic responses to acute exhaustive exercise, but alterations of the correlation between central autonomic and peripheral sympathetic activity may indicate a different sympathetic reactivity after exercise in patients with epilepsy. The clinical relevance of this finding and its modulators (seizures, anti-seizure medication, etc.) still needs to be elucidated.

Impact of moderate aerobic exercise on small-world topology and characteristics of brain networks after sport-related concussion: an exploratory study - Coenen, Jessica; Strohm, Michael; Reinsberger, Claus (Scientific Reports)
Abstract Sport-related concussion (SRC) is a complex brain injury. By applying graph-theoretical analysis to networks derived from neuroimaging techniques, studies have shown that despite an overall retention of small-world topology, changes in small-world properties occur after brain injury. Less is known about how exercise during athletes’ return to sport (RTS) influences these brain network properties. Therefore, in the present study dense electroencephalography (EEG) datasets were collected pre- and post-moderate aerobic exercise. Small-world properties of whole brain (WB) and the default mode network (DMN) were extracted from the EEG datasets of 21 concussed athletes and 21 healthy matched controls. More specifically, path length (LP), clustering coefficient (CP), and small-world index (SWI) in binary and weighted graphs were calculated in the alpha frequency band (7–13 Hz). Pre-exercise, SRC athletes had higher DMN-CP values compared to controls, while post-exercise SRC athletes had higher WB-LP compared to controls. Weighted WB analysis revealed a significant association between SRC and the absence of small-world topology (SWI ≤ 1) post-exercise. This explorative study provides preliminary evidence that moderate aerobic exercise during athletes’ RTS induces an altered network response. Furthermore, this altered response may be related to the clinical characteristics of the SRC athlete.

Differences in Network Functional Connectivity in Response to Sub-Symptomatic Exercise Between Elite Adult Athletes after Sport-Related Concussion and Healthy Matched Controls: A Pilot Study - Coenen, Jessica; van den Bongard, Franziska; Delling, Anne Carina; Reinsberger, Claus (Journal of Neurotrauma)

Advancing concussion research – follow the yellow brick road - Reinsberger, Claus; Gardner, Andrew J. (Journal of Science and Medicine in Sport)

Kopfverletzungen: Was der Teamarzt wissen sollte Head injuries: What the team physician needs to know - Oesterschlink, Julian; Reinsberger, Claus (Die Orthopädie)

Übergänge gestalten - Breckner, Anne

„Lob des Bastards“ oder: Performative Praktiken des Grenzgangs. Michael Roes‘ west-östlicher Macbeth: Someone is Sleeping in my Pain (2001)/Nah Inverness (2004). - Eke, Norbert (Der neue Weltengarten. Jahrbuch für Literatur und Interkulturalität 2023.)

Model-based impact analysis in dynamic System of Systems - Gräßler, Iris; Wiechel, Dominik; Rarbach, Sven (Procedia CIRP)

Explain with, rather than explain to: How explainees shape their own learning - Fisher, Josephine Beryl; Rohlfing, Katharina J.; Donnellan, Ed; Grimminger, Angela; Gu, Yan; Vigliocco, Gabriella (Interaction Studies)
Research about explanation processes is gaining relevance because of the increased popularity of artificial systems required to explain their function or outcome. Following an interactive approach, not only explainers, but also explainees contribute to successful interactions. However, little is known about how explainees actively guide explanation processes and how their involvement relates to learning. We explored the occurrence and type of explainees’ questions in 20 adult — adult explanation dialogues about unknown present and absent objects. Crucially, we related the question types to the explainees’ subsequent recall of the unknown object labels. We found that explainees asked different types of questions, especially about the object’s label and facts. Questions about the object’s function were asked more when objects were present. In addition, requests for labelling were linked to better recall. The results contribute to designing explainable AI that aims to provide relevant and adaptive explanations and to further experimental approaches to study explanations.

Open Edirom: From hybrid music edition to open data publication - Frömmel, Lena; Bachmann, Tobias; Plaksin, Anna Viktoria Katrin; Münzmay, Andreas (Proceedings of the 11th International Conference on Digital Libraries for Musicology)
The OPEN Edirom project is developing a digital edition of incidental music for Goethe’s play Faust, representing an innovative initiative within the realm of music philology and MEI/TEI edition. Embracing the "data first" principle, OPEN Edirom prioritizes making its content openly accessible, thereby enabling diverse potential uses for researchers and performers. Our aim involves presenting the scholarly text and music edition in its entirety, incorporating its various forms of data, i.e. music, texts, source images, metadata, and annotations, all displayed with Edirom software. The piece we edit in this project is Goethe’s renowned play Faust I, as adapted by Carl Seydelmann, along with the corresponding music composed by Peter Joseph von Lindpaintner for the Court Theatre in Stuttgart. The work premiered in 1832. This paper delves into the concept of music edition as open data publication and delineates its advantages over analog and hybrid editions in terms of reusability and alignment with the FAIR principles. It also addresses the challenges encountered in data preparation, both specific to incidental music and in general data processing. Furthermore, we propose solutions and recommendations for similar projects based on our insights.